2017
DOI: 10.5098/hmt.8.12
|View full text |Cite
|
Sign up to set email alerts
|

G-Jitter Effects on the Mixed Convection Flow of Nanofluid Past an Inclined Stretching Sheet

Abstract: Mixed convection flows of nanofluid past an inclined stretching sheet with g-jitter effect is studied in this paper. Water based nanofluid containing copper, copper oxide, aluminium oxide and silver nanoparticles are concerned. Coupled nonlinear partial differential equations are solved using Kellerbox method. The effect of solid nanoparticles volume fraction parameter, frequency of oscillation and inclination angle parameter is observed to reduce the skin friction and heat transfer coefficients whereas mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…In recent years, a wide research work has been done in this research area to understand the thermo-hydraulic behavior of this new heat transfer fluid generation, they proved that nanoparticles suspension within the conventional heat transfer fluid increases its thermal conductivity and consequently improves the heat transfer (Rawi et al, 2017;Wakif et al, 2017;Ramesh and Gireesha, 2017). Al-Rashed et al (2017) studied the effect of magnetic field on natural convection inside a cubical cavity filled with CNT -water nanofluide; they found that for all the Rayleigh numbers the Bejan number increase by increasing nanoparticles volume concentration.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a wide research work has been done in this research area to understand the thermo-hydraulic behavior of this new heat transfer fluid generation, they proved that nanoparticles suspension within the conventional heat transfer fluid increases its thermal conductivity and consequently improves the heat transfer (Rawi et al, 2017;Wakif et al, 2017;Ramesh and Gireesha, 2017). Al-Rashed et al (2017) studied the effect of magnetic field on natural convection inside a cubical cavity filled with CNT -water nanofluide; they found that for all the Rayleigh numbers the Bejan number increase by increasing nanoparticles volume concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Choi (1995) originally proposed the concept of nanofluid (Fig. 3), which is a fluid with some types of Nano-metric particles suspended in a base fluid like water, engine oil, and ethylene glycol (Rawi et al, 2017). Examples of nanoparticles are carbide ceramics (SiC, TiC), nitride ceramics (AlN, SiN), alloyed nanoparticles (Al70, Cu30), metals (Cu, Ag, Au), semiconductors (TiO2, SiC), single, double or multi walled carbon nanotubes, metallic oxides (Al2O3, CuO), etc.…”
Section: Nanofluidmentioning
confidence: 99%